Analysis of fatty acid composition and sensitivity to dietary n-3 PUFA intervention of mouse n-3 PUFA-enriched tissues/organs. (May 2023) - Zhang, Hui; He, Yannan; Song, Chunyan; Chai, Zhenglong; Liu, Chundi; Sun, Shuben; Huang, Qiuhan; He, Canxia; Zhang, Xiaohong; Zhou, Yuping; Zhao, Feng
Highlights: Eight tissues and organs of mice have obvious tissue selectivity for n-3 PUFA including three brain regions and five peripheral tissues/organs (tongue, quadriceps, gastrocnemius, kidney, and heart). The tongue has a great selectivity for n-3 PUFA. n-3 PUFA interventions led to a significantly decreased arachidonic acid level in the n-3 PUFA-enriched peripheral organs, including the kidney, quadriceps, and the tongue. Peripheral organs enriched with n-3 PUFA are more sensitive to EPA interventions and are more likely to be affected by dietary EPA. Abstract: Purpose: n-3 polyunsaturated fatty acids (PUFAs), docosahexaenoic acid (DHA; C22:6 n3) and eicosapentaenoic acid (EPA; C20:5 n3), are of concern for their health-promoting effects such as anti-inflammatory, but the tissue selectivity for n-3 PUFA (i.e., which tissues and organs are rich in n-3 PUFA) is still not well known. In addition, it is unclear which tissues and organs are more sensitive to n-3 PUFA intervention. These unresolved issues have greatly hindered the exploring of the health benefits of n-3 PUFA. Methods: Twenty-four 7-week-old male C57BL/6 J mice were assigned to the control, fish oil, DHA, and EPA groups. The last three groups were given a 4-week oral intervention of fatty acids in ethyl ester (400 mg/kg bw). The fatty acid profiles in 27 compartments were determined by gas chromatography. Results: The proportion of long-chain n-3 PUFA (the total relative percentage of EPA, DPA n3, and DHA) was analyzed. Eight tissues and organs, including the brain (cerebral cortex, hippocampus, hypothalamus) and peripheral organs (tongue, quadriceps, gastrocnemius, kidney, and heart) were determined as being n-3 PUFA-enriched tissues and organs, owing to their high n-3 PUFA levels. The highest n-3 PUFA content was observed in the tongue for the first time. Notably, the content of linoleic acid (LA; C18:2 n6c) in peripheral organs was observed to be relatively high compared with that in the brain. Interestingly, the proportions of EPA in the kidney, heart, quadriceps, gastrocnemius, and tongue increased more markedly after the EPA intervention than after the DHA or fish oil intervention. As expected, the levels of proinflammatory arachidonic acid (AA; C20:4 n6) in the kidney, quadriceps, and tongue were markedly decreased after the three dietary interventions. Conclusion: Peripheral tissues and organs, including the tongue, quadriceps, gastrocnemius, kidney, and heart, besides the brain, showed obvious tissue selectivity for n-3 PUFA. In the whole body of mice, the tongue exhibits the strongest preference for n-3 PUFA, with the highest proportion of n-3 PUFA. Moreover, these peripheral tissues and organs, especially the kidney, are more sensitive to dietary EPA administration in comparison with the brain. Graphical abstract: Image, graphical abstract